Arabic metalinguistic knowledge predicts reading comprehension: A scoping review - Bin Sawad, Nouf; Law, Jeremy M.; Tibi, Sana; Boese, Karen (Frontiers in Communication, 2022)
Arabic is a language with unique characteristics, yet the role metalinguistic skills (i.e., phonological awareness, morphological awareness, and orthographical knowledge) play in the development of reading and reading comprehension in Arabic is not well understood. This review aims to: 1) synthesise studies that examine metalinguistic skills’ contribution to reading comprehension in Arabic, 2) emphasise gaps and limitations within the current body of literature, and 3) offer recommendations for further research. This review followed Arksey and O’Malley’s (2005) five-stage methodological framework to identify studies. Sixteen studies examined the relation between metalinguistic skills and reading comprehension in Arabic. These studies involved students in grades 1 to 12. Morphological awareness was found to be the strongest predictor of reading comprehension among Arabic children; in addition, phonological awareness and phonemic diacritics were found to be associated with reading comprehension in early grades. Lastly, this review identified a significant gap in the literature, as few studies have investigated orthographical knowledge in relation to Arabic reading development and outcomes. This literature review supports the claim that metalinguistic variables can predict reading comprehension among Arabic readers. Yet, the generalisation of findings is cautioned due to the influences of dialect and the small number of studies involved in the review. These results are discussed in relation to the current teaching guidelines for instructing Arabic reading comprehension.